2011
DOI: 10.1242/jeb.062356
|View full text |Cite
|
Sign up to set email alerts
|

Induced and constitutive responses of digestive enzymes to plant toxins in an herbivorous mammal

Abstract: SUMMARYMany plants produce plant secondary compounds (PSCs) that bind and inhibit the digestive enzymes of herbivores, thus limiting digestibility for the herbivore. Herbivorous insects employ several physiological responses to overcome the anti-nutritive effects of PSCs. However, studies in vertebrates have not shown such responses, perhaps stemming from the fact that previously studied vertebrates were not herbivorous. The responses of the digestive system to dietary PSCs in populations of Bryantʼs woodrat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…different diets require different digestive conditions, enzymes, or detoxification mechanisms for efficient assimilation (Afik & Karasov ; Karasov et al . ; Kohl & Dearing ; Barceló et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…different diets require different digestive conditions, enzymes, or detoxification mechanisms for efficient assimilation (Afik & Karasov ; Karasov et al . ; Kohl & Dearing ; Barceló et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of a wide range of resources that differ in quality result in physiological trade-offs associated with resource digestion; e.g. different diets require different digestive conditions, enzymes, or detoxification mechanisms for efficient assimilation (Afik & Karasov 1995;Karasov et al 2011;Kohl & Dearing 2011;Barcel o et al 2016). Thus, nutritional differences in the energy and macromolecular content among diet items may impact digestive performance, which could affect energy budgets when animal are faced with the prospect of switching diets.…”
Section: Introductionmentioning
confidence: 99%
“…Herbivorous grouse species specialize on a number of plants that are relatively high in fiber and rich in plant secondary metabolites (PSMs), and so might be faced with limited digestibility associated with both fiber and toxins. We have previously shown that some PSMs, such as phenolics and monoterpenes can inhibit digestive enzymes (Kohl and Dearing 2011;Kohl et al 2015). Though, the enzymes of grouse can be more resistant to inhibition by PSMs when compared to domestic chicken (Kohl et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…changing from few daily meals with high food intake to many meals with low food intake, 19,20 and metabolization and detoxification of toxic PSM taken up with food. [21][22][23][24][25] Another adaptation to PSM that cannot be taken up in unlimited amounts is the evolutionary developments of specialists and generalists. The mixed diet of generalistic herbivores reduce the need for detoxification of similar groups of toxic PSM, whereas herbivores specialist to one or few plant species as food source developed especially improved metabolic detoxification pathways.…”
Section: Plant Defense Systems Against Herbivoresmentioning
confidence: 99%